2002
DOI: 10.1007/s11745-002-0872-8
|View full text |Cite
|
Sign up to set email alerts
|

Maternal supplementation with CLA decreases milk fat in humans

Abstract: CLA refers to isomers of octadecadienoic acid with conjugated double bonds. The most abundant form of CLA (rumenic acid (RA): c9,t11-18:2) is found in milk and beef fat. Further, CLA supplements containing RA and t10,c12-18:2 are now available. Consumption of commercially produced CLA has been shown to decrease adipose accretion in growing laboratory and production animals and cause milk fat depression in cows. We tested the hypothesis that CLA supplementation would increase milk CLA concentration and decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
6
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 23 publications
5
56
6
1
Order By: Relevance
“…The t10,c12 CLA isomer is at most a minor dietary component and was essentially absent from plasma PC and CE at baseline. The fractional concentrations of both CLA isomers at baseline in PC and CE were comparable to those reported previously for total plasma lipids (22,26,28,30) and for plasma PC (22), but c9,t11 CLA concentration at baseline in the CE fraction was ‫-3ف‬fold greater than that reported previously (22).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The t10,c12 CLA isomer is at most a minor dietary component and was essentially absent from plasma PC and CE at baseline. The fractional concentrations of both CLA isomers at baseline in PC and CE were comparable to those reported previously for total plasma lipids (22,26,28,30) and for plasma PC (22), but c9,t11 CLA concentration at baseline in the CE fraction was ‫-3ف‬fold greater than that reported previously (22).…”
Section: Discussionsupporting
confidence: 85%
“…All studies in humans reported to date have used mixtures of CLA isomers typically containing predominantly c9,t11 CLA and t10,c12 CLA in different ratios together with smaller amounts of other isomers. These range from relatively pure preparations containing c9,t11 CLA and t10,c12 CLA in ratios of 50:50 or 80:20 (22,(25)(26)(27)(28) to complex mixtures (23,29,30). Thus, the dose of individual isomers may be relatively low despite high intakes of total CLA compared with the basal diet.…”
mentioning
confidence: 99%
“…Milk fat content was also significantly lower during CLA supplementation in breastfeeding women. Therefore it should not be consumed during lactation (Masters et al 2002).…”
Section: Cla and Lipidsmentioning
confidence: 99%
“…In fact, the National Research Council in 1996 stated that CLA (or forms, thereof) is the only fatty acid shown unequivocally to inhibit carcinogenesis in experimental animals [6]. In addition to having anticarcinogenic properties, investigators using mixed isomers of CLA have reported antiatherosclerotic properties, effects on glucose tolerance, alterations in growth or body composition, and milk fat depression [7][8][9][10][11][12]. Some studies also suggest adverse effects of CLA on health such as those relating to decreasing HDL cholesterol, Lp(a), and endothelial function [13][14][15].…”
mentioning
confidence: 99%